2016
DOI: 10.1177/0021998316682309
|View full text |Cite
|
Sign up to set email alerts
|

Mode I fracture toughness of CFRP as a function of temperature and strain rate

Abstract: Composite structures currently used in the automotive industry must meet strict requirements for safety reasons. They need to maintain strength under varied temperatures and strain rates, including impact. It is therefore critical to fully understand the impact behaviour of composites. This work presents experimental results regarding the influence of a range of temperature and strain rates on the fracture energy in mode I, GIC, of carbon fibre reinforced plastic plates. To determine GIC as a function of tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 42 publications
(45 reference statements)
2
34
0
Order By: Relevance
“…The elastic mechanical properties of the used material were previously determined in the work of Campilho . Also, the complete cohesive properties of the CFRP, determined at quasi‐static conditions (1 and 100 mm/min), were previously determined by the authors …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The elastic mechanical properties of the used material were previously determined in the work of Campilho . Also, the complete cohesive properties of the CFRP, determined at quasi‐static conditions (1 and 100 mm/min), were previously determined by the authors …”
Section: Methodsmentioning
confidence: 99%
“…39 Also, the complete cohesive properties of the CFRP, determined at quasi-static conditions (1 and 100 mm/min), were previously determined by the authors. [40][41][42][43]…”
Section: Materials and Propertiesmentioning
confidence: 99%
“…One of the few known work regarding the impact characterization of CFRP in which the G IC was experimentally determined, was performed by the authors. 25 As only experimental data are available for the case of quasi-static conditions, 22,26 the mechanical properties of CFRP under impact were not considered to be strain rate dependent in the numerical models, and were based on the quasi-static values ( Table 2).…”
Section: Experimental Details Cfrp Mechanical Propertiesmentioning
confidence: 99%
“…[15][16][17] Numerical analyses of composite plates under an impact load were performed by several authors [18][19][20] with good agreement with the experimental results. The use of cohesive elements to simulate the behaviour of composite materials has been studied, [21][22][23][24] allowing to conclude that such integration is able to correctly assess the G IC behaviour. Numerical studies regarding the measurement of G IC of composite materials are not currently available in the literature for the case of impact conditions, which then constitutes a field to explore.…”
Section: Introductionmentioning
confidence: 99%
“…Fibre-reinforced polymer composites have also been subjected to the destructive tests under different strain rates to evaluate their mechanical response [25][26][27]. It was found that while the tensile properties of unidirectional composites, dominated by the fibre, were not affected by the strain rate, the opposite was the case for the transverse direction, dominated by the matrix, [28][29][30].…”
Section: Introductionmentioning
confidence: 99%